1999
DOI: 10.1046/j.1365-2435.1999.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and water fluxes in Beech–Spruce model ecosystems in response to long‐term exposure to atmospheric CO2 enrichment and increased nitrogen deposition

Abstract: 1. We present data on the gas exchange of 32 Beech–Spruce model ecosystems including understorey species, which were planted on acidic or calcareous soil in 16 (half‐split) open‐top chambers in 1994 and were continuously exposed to the combinations of two CO2 concentrations and two wet nitrogen deposition rates for 3 years. 2. Instantaneous mid‐season net ecosystem carbon‐exchange rates (NEC) were determined during the day (11.00–16.00 h, NECd) and at night (22.00–02.00 h, NECn) with a mobile chamber in July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Our results indicated that ecosystem ET was independent of N addition rates, suggesting that ecosystem-level water flux in this grassland ecosystem may not be greatly affected by N addition. This is supported by some previous studies (Maurer et al 1999;St Clair et al 2009). These results suggest that water balance in this semi-arid grassland ecosystem may be mainly governed by solar radiation, wind and temperature other than soil nutrients.…”
Section: R E S P O N S E S O F E C O S Y S T E M W a T E R F L U X A supporting
confidence: 91%
“…Our results indicated that ecosystem ET was independent of N addition rates, suggesting that ecosystem-level water flux in this grassland ecosystem may not be greatly affected by N addition. This is supported by some previous studies (Maurer et al 1999;St Clair et al 2009). These results suggest that water balance in this semi-arid grassland ecosystem may be mainly governed by solar radiation, wind and temperature other than soil nutrients.…”
Section: R E S P O N S E S O F E C O S Y S T E M W a T E R F L U X A supporting
confidence: 91%
“…This is supported by a greater mineralization of native C in the calcareous sand (Fig. 3) and by a 50% increase in respiration measured by the nightly CO 2 efflux (Maurer et al . 1999).…”
Section: Discussionmentioning
confidence: 72%
“…Photosynthetic rates in our model communities were increased in elevated CO 2 both at the leaf and canopy level (Egli et al 1998;Maurer et al 1999), but Egli et al (1998Egli et al ( , 2001 also detected partial downward adjustment of photosynthesis throughout the experiment. This effect was more pronounced on the nutrient-poor acidic soil and stronger for Fagus than for Picea.…”
Section: Temporal Patterns In Tree Growthmentioning
confidence: 71%